Methods to quantify and reduce rotor losses in a solid rotor yoke permanent magnet machine - Wills, Dominic (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Electrical and Electronic Engineering))--University of Stellenbosch, 2010.